Switching to insulin glargine 300 units/mL in real‐world older patients with type 2 diabetes (DELIVER 3). Issue 11 (18th July 2019) - Bailey, Timothy S.; Wu, Jasmanda; Zhou, Fang L.; Gupta, Rishab A.; Menon, Arjun A.; Berhanu, Paulos; Westerbacka, Jukka; Van Vleet, John; Blonde, Lawrence
Abstract: Aim: To compare the second‐generation basal insulin glargine 300 units/mL (Gla‐300) and first‐generation basal insulins on glycaemic control and hypoglycaemia risk in older adults with type 2 diabetes (T2D). Materials and methods: DELIVER 3 was a retrospective observational cohort study of electronic medical records. A total of 1176 older adults (aged ≥ 65 years) with T2D and ≥1 HbA1c value during 6 month baseline and 3 to 6 month follow‐up who switched from basal insulin to Gla‐300 were propensity score‐matched to 1176 older adults who switched to a first‐generation basal insulin [insulin detemir (IDet) or insulin glargine 100 units/mL (Gla‐100)]. Outcomes were follow‐up HbA1c, achievement of HbA1c <7% and <8%, hypoglycaemia incidence and event rates, and healthcare resource utilization. Results: Following basal insulin switching, HbA1c reductions were greater/similar with Gla‐300 versus IDet/Gla‐100 (variable follow‐up: −0.45% ± 1.40% vs. −0.29% ± 1.57%; P = .021; fixed follow‐up: −0.48% ± 1.49% vs. −0.38% ± 1.59%; P = .114), while HbA1c goal attainment was similar in both cohorts. Gla‐300 was associated with less hypoglycaemia [event rate: adjusted rate ratio (aRR): 0.63, 95% CI: 0.53‐0.75; P < .001] and inpatient/emergency department‐associated hypoglycaemia (adjusted hazard ratio: 0.58, 95% CI: 0.37‐0.90; P = .016; aRR: 0.43, 95% CI: 0.31‐0.60; P < .001) by variable follow‐up. By fixed follow‐up, hypoglycaemia results significantly or numerically favoured Gla‐300. Conclusion: Among older adults with T2D, switching to Gla‐300 versus Gla‐100/IDet was associated with greater/similar improvements in glycaemic control, and generally less hypoglycaemia.